Quantifying the Impacts of Capturing Territory from the Government in the Republic of Yemen - Tandon, Sharad (World Bank, Washington, DC, 2018)
This article estimates how households were aﬀected by the mostly non-violent capture of Yemen’s capital in 2014 using a survey conducted as the capital was captured. Although socioeconomically advantaged households were initially better able to cope with the shock than other households, the capture resulted in a robust decline in expenditure for the entire population within three months. Struggling households turned to a number of coping strategies to meet their basic needs- they increasingly made purchases on credit, increased their reliance on self-employment to deal with a decline in the economic climate, and reduced both the quantity and quality of foods consumed. Furthermore, women were aﬀected by the capture more so than men. These results demonstrate that the capture of territory without wide-spread violence can result in a nearly immediate decline in standards of living and further illustrate the manners in which households were able to cope with the shock.